Changes in alcohol purchases from grocery stores after authorising the sale of stronger beverages: The case of the Finnish alcohol legislation reform in 2018. Issue 6 (December 2022) - Uusitalo, Liisa; Nevalainen, Jaakko; Rahkonen, Ossi; Erkkola, Maijaliisa; Saarijärvi, Hannu; Fogelholm, Mikael; Lintonen, Tomi
Aims: The Finnish alcohol law was reformed in January 2018. The availability of alcoholic beverages in grocery stores increased as the legal limit for retail sales of alcoholic drinks was raised from 4.7% to 5.5% alcohol, and the requirement of production by fermentation was abolished. We analysed how the inclusion of strong beers, ciders, and ready-to-drink beverages in grocery stores was reflected in alcohol purchases, and how these changes differed by age, sex, level of education and household income.Design: The study sample included 47, 066 loyalty card holders from the largest food retailer in Finland. The data consisted of longitudinal, individual-level information on alcohol purchases from grocery stores, covering the time period between 1 January 2017 and 31 December 2018. The volumes of absolute alcohol during a calendar year from beers, ciders, ready-to-drink beverages, and in total, were calculated. Alcohol purchases in 2017 and 2018 were compared.Results: There was no overall change in the total alcohol (0.04 [95% CI −0.03, 0.11] litres/year) or beer purchases (−0.05 [95% CI −0.11, 0.02] litres/year). Purchases of ready-to-drink beverages increased by 0.10 [95% CI 0.09, 0.11] litres/year (+ 84%). Total alcohol purchases increased in the three highest income groups, whereas they decreased in the two lowest groups ( p for the interaction < 0.0001).Conclusions: The increased purchases of alcohol as ready-to-drink beverages were, on the average, compensated for by a decrease in purchases of other alcoholic beverages. Higher prices probably limited the purchases among lower income groups and younger consumers, while the increase was sharper in higher income groups.